2016
DOI: 10.1097/mca.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Thin-cap fibroatheroma and large calcification at the proximal stent edge correlate with a high proportion of uncovered stent struts in the chronic phase

Abstract: TCFA and large calcification at the proximal stent edge are strong predictors of uncovered stent struts. OCT is useful for selecting stent landing sites in terms of future occurrence of uncovered stent struts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…The effect of underlying plaque on stent strut coverage has not been well characterized. Some previous studies reported that neointima or stent strut coverage was less on a thin‐cap fibroatheroma 25,26 . In contrast, a recent OCT study demonstrated that percent covered struts and percent neointima were significantly greater and thicker on a lipidic plaque 27 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effect of underlying plaque on stent strut coverage has not been well characterized. Some previous studies reported that neointima or stent strut coverage was less on a thin‐cap fibroatheroma 25,26 . In contrast, a recent OCT study demonstrated that percent covered struts and percent neointima were significantly greater and thicker on a lipidic plaque 27 .…”
Section: Discussionmentioning
confidence: 94%
“…Some previous studies reported that neointima or stent strut coverage was less on a thin‐cap fibroatheroma. 25 , 26 In contrast, a recent OCT study demonstrated that percent covered struts and percent neointima were significantly greater and thicker on a lipidic plaque. 27 In the present study, we compared lipid versus non‐lipid segments within the same lesions in the same patients because this allowed each patient to serve as his or her own control; and we observed more NIH and better stent strut coverage in a lipidic segment compared with a nonlipidic segment without difference of MLA at 6‐month follow‐up.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, the main features of vulnerable plaques were TCFA and a large lipid pool [ 18 ], which could influence post-stent outcomes, as reported by a clinical study [ 19 ]. Ueda et al [ 20 ] identified that lipid-rich plaques underlying stent edges were strong predictors of uncovered stent struts and that TCFA and large calcification at the proximal stent edge were strong predictors of uncovered stent struts at follow-up. In post-PCI OCT assessing 1002 lesions, suboptimal stent deployment, including in-stent minimal lumen area, distal reference lumen area, and dissection at the distal stent edge, was associated with an increased incidence of MACEs, which are a composite of all-cause death, MI, and target lesion revascularization during follow-up [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…After intracoronary administration of 1 mg of isosorbide dinitrate, pull‐back was performed during continuous injection of X‐ray contrast media or lactated low‐molecular‐weight dextran at 2.5–3.5 mL/s through the guiding catheter using an injection pump to remove blood from the field of view and to allow for clear visualization of the vessel wall. Images were acquired at 5 frames/mm and an automated pull‐back speed of 20 mm/s …”
Section: Methodsmentioning
confidence: 99%